Transforming Postmenopausal Healthcare: Leveraging Telemedicine and AI-Driven Predictive Analytics for Personalized Wellness – A Scoping Review (International Journal of Physiotherapy, 2025)
Background: A woman is considered "postmenopausal" if she has not had a menstrual period for at least a year and is neither pregnant nor nursing. Postmenopausal hormone levels continue to fluctuate and decline, leading to common postmenopausal symptoms like hot flashes, vaginal dryness, decreased libido, mood swings, sleep disturbances, and an increased risk of osteoporosis, cardiovascular diseases, and weight gain. Estrogen deficiency can also lead to cognitive changes, urinary incontinence, back pain, and increased risk of musculoskeletal disorders, including disc degeneration and osteoporosis. Strength training and aerobic exercises have been shown to reduce back pain and disability, while anxiety, stress, and fear can exacerbate overall disability. Staying physically active is highly recommended for mitigating the effects of hormonal changes and improving overall health outcomes.Methods: This scoping review examines the role of artificial intelligence and telemedicine in physiotherapy exercise programs for postmenopausal women. Data were gathered from peer-reviewed journals, clinical trials, and existing telemedicine and AI applications in healthcare. The methods focused on: Evaluating AI-based tools that assist in exercise monitoring, personalization, and adherence tracking for postmenopausal women and assessing telemedicine platforms that facilitate remote physiotherapy consultations and exercise guidance.Results: The analysis revealed that AI and telemedicine offer significant benefits for managing postmenopausal symptoms through physiotherapy.Conclusion: Regular physical activity, supported by AI and telemedicine, is essential for mitigating the risks of musculoskeletal disorders, osteoporosis, and other postmenopausal challenges. By providing personalized, accessible, and effective solutions, these technologies address common symptoms and improve quality of life.